Design modification of a porcelain-fused-to-metal (PFM) adhesive bridge for a mandibular molar with a short clinical crown: A case report - Amelia, Amelia; Bonifacius, Setyawan; Rakhmatia, Yunia Dwi (Universitas Padjadjaran, 2026)
Introduction: Replacement of a single missing posterior tooth can be effectively achieved using a fixed dental prosthesis (FDP). Resin-bonded FDPs provide a conservative alternative to conventional full-coverage FDPs because they require minimal tooth reduction and preserve the remaining tooth structure while maintaining function and aesthetics. However, short clinical crowns and lingually inclined mandibular molars may compromise retention, resistance, and the path of insertion. This case report describes the use of a modified porcelain-fused-to-metal (PFM) resin-bonded FDP with onlay metal wings and adhesive bonding to manage a mandibular molar with a short clinical crown and a lingually inclined abutment. Case report: A 25-year-old male patient was referred to the Prosthodontics Clinic for replacement of a missing mandibular right first molar. The tooth had been extracted approximately one year previously. Intraoral examination showed that tooth 47 was lingually inclined and had a short clinical crown. Panoramic radiography showed adequate bone support and no pathological findings, indicating that the abutment teeth were suitable for prosthetic treatment. The treatment plan involved a modified PFM adhesive bridge with a sanitary pontic replacing tooth 46 and onlay metal wings on teeth 45 and 47. Retention was achieved through a combination of mechanical interlocking, chemical bonding, and adhesive cementation. At the one-week follow-up after FDP insertion, the prosthesis demonstrated satisfactory fit and occlusion, and the patient reported no discomfort or functional problems. Conclusion: A modified onlay-wing design for a lingually inclined abutment with a short clinical crown, combined with adhesive resin cementation to a metal framework, may provide a simplified and predictable approach for replacing a mandibular molar using a resin-bonded FDP.